PROSES PENGUNGKAPAN DIRI (SELF DISCLOSURE) KAUM GAY DALAM MENCARI PASANGAN PADA APLIKASI TINDER - Giga Nanda, Kadek Awidya; Sugiarica Joni, I Dewa Ayu; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2018)
ABSTRACT                Some Indonesian people still consider that sexual, bisexual and other sex behaviors which are incompatible with religious and cultural norms as deviant behavior. Currently, homosexuality is still considered to be something distorted because this kind of sexual behavior can not be treated generally and not acceptable to society. This condition can make gay individuals can not open themselves freely and affect the process of gay self-disclosure in the looking for a partner. The process of gay self-disclosure in looking for a partner can also be seen from the access to media information and gay community in Indonesia. Moreover, the sophistication of the global world today, gays have the convenience to be able to download applications, and facilitate them in the process of interaction and looking for a partner, in this case the researcher focus on Tinder application. This study aims to find how the process of gays self-disclosure in looking for a partner on Tinder application. The method of this study is qualitative method and post-positivism paradigm. The results of this study is the gays are more frank in the process of self-disclosure on Tinder application with the duration of conversation is 2 days to 10 days from the results. The informers indicate that the gays prefer to open themselves further in a self-disclosure in the Personal Messenger application, such as line and whatsapp aplication, and the gays that are Tinder users have different conversational intensity at doing thier self-disclosure as a couple-seeking process and relationship development process on Tinder application. Where the difference is the way to build a comfortable atmosphere in a conversation so that the process of relationship formation goes well and expected deeper.   Keywords: Couple-Seeking, Self-Disclosure, The Gays, Tinder Application